2015
DOI: 10.1039/c5ay01848j
|View full text |Cite
|
Sign up to set email alerts
|

Application of Oracet Blue in a novel and sensitive electrochemical biosensor for the detection of microRNA

Abstract: MicroRNAs in serum/plasma, have been introduced as a novel, reliable and specific biomarkers for detection, status monitoring and population screening of a disease. Along with the molecular biology techniques, electrochemical biosensors have become the major biosensing methods for miRNA quantification. Here we have tried to develop an electrochemical biosensing system which is simple, easy to prepare, highly sensitive and selective, cost-effective and no need for sample preparation and/or amplification. We hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 45 publications
0
26
1
Order By: Relevance
“…After modification of the working electrode with the EGO and GNWs, a 3.0 ml of 220.0 nM solution of thiolated SSDNA probes was placed on the electrode and kept in the humid container for 90 min to be attached on the surface of GNWs. After a mild double-distilled water wash, the modified electrode was immersed in the solution of MCH and was washed again [51]. The prepared nanobiosensor was used for quantification of the target miRNA in the solution for the required concentration.…”
Section: Nanobiosensor Fabrication and Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…After modification of the working electrode with the EGO and GNWs, a 3.0 ml of 220.0 nM solution of thiolated SSDNA probes was placed on the electrode and kept in the humid container for 90 min to be attached on the surface of GNWs. After a mild double-distilled water wash, the modified electrode was immersed in the solution of MCH and was washed again [51]. The prepared nanobiosensor was used for quantification of the target miRNA in the solution for the required concentration.…”
Section: Nanobiosensor Fabrication and Characterizationmentioning
confidence: 99%
“…The prepared nanobiosensor was used for quantification of the target miRNA in the solution for the required concentration. For this purpose, a 3.0 ml drop of the required concentration of target miRNA was dropped on the surface of the modified electrode and was kept isolated for 90 min and washed with the washing solution [51]. The hybridized nanobiosensor was immersed in the 0.095 mM solution of Dox for 11 min to allow the Dox molecule being intercalated in the double-strand structure.…”
Section: Nanobiosensor Fabrication and Characterizationmentioning
confidence: 99%
“…Besides, their nanobiosensor exhibits excellent selectivity and reproducibility, along with the great response on the human plasma as a real sample environment. Their achievements were superior compared to their previous study which was basically based on thiolated capture probes on the gold electrode using Oracet Blue as an electroactive label which had led to the dynamic range from 50.0 pM to 15.0 nM with a detection limit of 13.5 pM In Figure , experimental steps for the study are shown…”
Section: Micrornas As Cancer Biomarkersmentioning
confidence: 92%
“…For isolating the serum, the blood samples were allowed to clot in the absence of anticoagulant and simply centrifuged with recovery of supernatant. The serum samples were kept as 300 µL aliquots at −80 °C until further processing [59]. Using a Trizol-based method, total miRNA was isolated and subjected to qRT-PCR (as the gold standard method) for miR-106a detection.…”
Section: Methodsmentioning
confidence: 99%